2020
DOI: 10.1037/ort0000403
|View full text |Cite
|
Sign up to set email alerts
|

Neighbors as distal support for individuals with serious mental illnesses.

Abstract: Social networks are regarded as an asset to community integration. While family and friends provide important sources of support, familiar strangers like neighbors can facilitate support through anonymous, but meaningful interactions. Among individuals with serious mental illnesses (SMI), these interactions can help to compensate for increased social isolation and smaller networks of peers. This study explores whether neighbors can play a unique role in decreasing loneliness and bolstering a sense of community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The original aim of the review was to compare the impact of informal and formal care on people with SMI living in SA. The role of informal carers is under explored in current literature, even though informal care networks such as family involvement ( Allen et al, 2013 ; Dorer et al, 2009 ; Fossey et al, 2006 ) or supportive neighbourhoods ( Kriegel et al, 2019 ) are indicated as beneficial to people with SMI’s social participation and recovery. The review focuses on level of support and the authors acknowledge there are other factors that can influence participation for people with SMI living in SA including whether people are living in congregate settings or alone, and length of stay in accommodation which needs to be a consideration for future reviews.…”
Section: Limitationsmentioning
confidence: 99%
“…The original aim of the review was to compare the impact of informal and formal care on people with SMI living in SA. The role of informal carers is under explored in current literature, even though informal care networks such as family involvement ( Allen et al, 2013 ; Dorer et al, 2009 ; Fossey et al, 2006 ) or supportive neighbourhoods ( Kriegel et al, 2019 ) are indicated as beneficial to people with SMI’s social participation and recovery. The review focuses on level of support and the authors acknowledge there are other factors that can influence participation for people with SMI living in SA including whether people are living in congregate settings or alone, and length of stay in accommodation which needs to be a consideration for future reviews.…”
Section: Limitationsmentioning
confidence: 99%
“…However, these relationships were not sufficient to differentially predict the impact of perceived stigma on psychological distress and sense of community at the nonurban versus urban level. Nevertheless, this research contributes to a growing body of literature on the impact of place on people with SMI (Doroud et al, 2018;Gonzales et al, 2018;Kriegel et al, 2020;Townley et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…This study is based upon the premise that welcoming places are likely to enhance community participation among individuals with SMI (Power & Bartlett, 2018) and create opportunities to facilitate connections and establish social networks (Kriegel et al, 2020). We believe this contributes to the literature in two fundamental ways.…”
Section: Discussionmentioning
confidence: 99%
“…Visiting different neighborhoods, particularly those with greater resources, appears to be associated with lower levels of depression (Traoré, Vuillermoz, Chauvin, & Deguen, 2020). Furthermore, social connections, even those that are categorized as “familiar strangers” have the potential to increase one’s sense of community and reduce feelings of loneliness (Kriegel, Townley, Brusilovskiy, & Salzer, 2020). It is our contention that for the community to contribute to health and well-being and to provide opportunity for participation and social connectedness, it must be welcoming to the whole person, that is, welcoming to those with mental illnesses.…”
mentioning
confidence: 99%